Spatial-temporal occurrence of contaminants of emerging concern in urban rivers in southern Brazil. (January 2023) - Arsand, Juliana Bazzan; Dallegrave, Alexandro; Jank, Louíse; Feijo, Tiago; Perin, Mauricio; Hoff, Rodrigo Barcellos; Arenzon, Alexandre; Gomes, Adriano; Pizzolato, Tânia Mara
Abstract: The widespread use and misuse of antibiotics and pesticides has been linked with several risks to the environment and human health. In the present report, the results of the monitoring of 64 pharmaceuticals and 134 pesticides occurrence in an urban river in Southern Brazil are presented and discussed. Sampling campaigns have covered the period 2016–2018. The identification and determination of the analytes were achieved by high-resolution mass spectrometry. The data were analyzed using chemometric tools to obtain spatial-temporal models. Toxicological evaluation was achieved using acute toxicity (zebrafish standardized protocol), and determination of risk quotient. Within the 198 analytes included in the targeted analysis method for surface water, 33 were identified in an urban river during 2 years of monitoring, being 20 pharmaceuticals and 13 pesticides. Using high-resolution mass spectrometry, a suspect screening approach was established in an un-target analysis. The evaluation was carried out using a data bank built from consumption data of drugs and pesticides, in the metropolitan region of Porto Alegre - RS and their respective metabolites. The suspect screening analysis done with a data bank with more than 1450 compounds results in 27 suspect findings. The target analysis results showed a continuous prevalence of non-steroidal anti-inflammatories, analgesics, antipyretics, beta-blockers, corticoids, and antibiotics. Regarding the pesticides, the main classes were fungicides, especially those from triazol and strobilurin classes. Graphical abstract: Image 1 Highlights: 2 years of contaminants of emerging concern monitoring in urban river are reported. 33 analytes were detected and confirmed (20 pharmaceuticals and 13 pesticides). 27 compounds were identified as suspect screening, including illicit drugs. Spatial-temporal data showed the increase of CECs along the population density.